Absorptive capacity versus distributive capability: The asymmetry of knowledge transfer. Issue 10 (3rd October 2016) - Whitehead, Kimberly K.; Zacharia, Zach G.; Prater, Edmund L.
Abstract : Purpose: The purpose of this paper is to disentangle the role of the source and recipient of knowledge in supply chain collaboration by providing evidence that the distributive capabilities of a source, working in conjunction with the absorptive capacity (AC) of a recipient, have direct and significant effects on levels of collaborative engagement between supply chain partners and indirect and significant effects on collaborative operational outcomes. Design/methodology/approach: This study utilises 310 surveys and structural equations modelling to provide empirical evidence to support the significance of the source of knowledge in collaborative activities. Findings: The study provides evidence for source-based knowledge transfer constructs (distributive capabilities) in supply chain collaboration. Further, this research supports these capabilities working in conjunction with recipient AC both as necessary but insufficient requirements for successful knowledge transfer. Practical implications: Firm interdependence within supply chains continues to grow. In today's environment of outsourcing and increasing levels of inter-firm activities, this research provides a parsimonious model of collaboration that allows firms to understand knowledge transfer better and how to more aptly manage these types of activities and complex relationships. Originality/value: Earlier research in this domain has focussed on the abilities of a recipient firm to absorb knowledge in order to understand successful collaborative knowledge transfer. By solely focussing on the recipient firm, the role of the source of knowledge has been largely overlooked in this stream of research.